Synthesis and anticonvulsant activity of some 2-pyrazolines derived from chalcones - KAYMAKÇIOĞLU, BEDİA; ARICIOĞLU, FEYZA (ELSEVIER SCIENCE BV, 2017)
Synthesis of chalcones (1,3-diarylprop-2-en-1-ones) and 2-pyrazoline derivatives has been an active field of research due to their established pharmacological effects. In this study, a series of chalcones were prepared with methyl aryl ketones and substituted aldehydes in the presence of sodium hydroxide and methanol through Claisen-Schmidt condensation. 3,5-Disubstituted4,5-dihydro-1H-pyrazole-1-carbothioamides were synthesized by refluxing selected chalcones and thiosemicarbazide in alkaline medium. Similarly N-3,5-trisubstituted-4,5-dihydro-1H-pyrazole-1-carboxamides were synthesized by refluxing selected chalcones with N-(4-chlorophenyl) semicarbazide in alkaline medium. Structures of the synthesized compounds were confirmed by elemental analysis and spectral (UV, IR, H-1 NMR, C-13 NMR, and mass) data, which were in line with the proposed structures. All compounds were tested for their anticonvulsant activity using pentylenetetrazole induced seizure (PTZ) and maximal electroshock seizure (MES) tests in mice at a dose level of 50 mg/kg. Among the 2-pyrazoline-1-carbothioamide derivatives, 5-(2,6-dichlorophenyl)-3-(thiophen-2-yl)-4,5-dihydro-1H-pyrazole-1-carbothioamide (2e) reduced grade-5 seizure activity and also increased survival rate in PTZ test. In MES test, 5-(4-methoxyphenyl)-3-[4-(methylsulphonyl) phenyl]-4,5-dihydro-1H-pyrazole-1-carbothioamide(2g) has not only decreased seizure severity, but also increased survival rate. Among the 2-pyrazoline-1-carboxamide derivatives, 3-(5-bromothiophen-2-yl)-N-(4-chlorophenyl)-5-(2,6-dichlorophenyl)-4,5-dihydro-1H-pyrazole-1-carboxamide (3d) having 5-bromothiophen and 2,6-dichlorophenyl moieties and N-(4-chlorophenyl)-5-(2,6-dichloro-phenyl)-3-(5-chlorothiophen-2-yl)-4,5-dihydro-1H-pyrazole-1-carboxamide (3e) having 5-chlorothiophen and 2,6-dichlorophenyl moieties showed remarkable activities in PTZ test. Among all tested derivatives, compound 3d was found to be the most active one and reduced grade-5 seizure severity and also increased survival rate. (C) 2013 Production and hosting by Elsevier B.V. on behalf of King Saud University.
Keywords: Chalcones; 2-Pyrazolines; Carbothioamide; Carboxyamide; Anticonvulsant activity; PHARMACOLOGICAL-PROPERTIES; DERIVATIVES; DRUGS